Biliary stents reshape the bile microbiome in the absence of cholangitis - Kayashima, Atsuto; Fukuhara, Seihiro; Miyamoto, Kentaro; Iwasaki, Eisuke; Kato, Motohiko; Sujino, Tomohisa (Endoscopy International Open, 2025)
Biliary stents are widely used in endoscopic retrograde cholangiopancreatography (ERCP), yet their impact on the native bile microbiome under non-infectious conditions remains unclear. We aimed to characterize stent-associated alterations in the biliary microbiome using 16S rRNA gene sequencing.We analyzed bile samples collected during ERCP from 35 patients without clinical or laboratory evidence of acute cholangitis. Patients were categorized into a control group (n = 25; naïve papillae) and an endoscopic biliary stenting (EBS) group (n = 10; previously stented). Microbial composition was assessed using high-throughput 16S rRNA sequencing after propensity score matching to balance background characteristics.Beta diversity differed significantly between groups (PERMANOVA, P < 0.01), despite no significant differences in alpha diversity. The EBS group demonstrated increased relative abundance of Firmicutes and Fusobacteriota, and depletion of Proteobacteria. Notably, Enterococcus was significantly enriched in the EBS group (log fold change 6.74; q < 0.01), whereas Sphingomonas was reduced.Endoscopic biliary stenting is associated with distinct bile microbiome alterations, characterized by enrichment of Enterococcus species in clinically stable patients. These findings suggest that stents may predispose to opportunistic colonization, providing a potential mechanistic link to future cholangitis. Recognizing such preclinical dysbiosis may inform tailored antimicrobial strategies and future stent design.
Keywords: Pancreatobiliary (ERCP/PTCD); Quality and logistical aspects; Hygiene; ERC topics